2016
DOI: 10.1002/jat.3304
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an air–liquid interface exposure system for assessing toxicity of airborne nanoparticles

Abstract: The use of refined toxicological methods is currently needed for characterizing the risks of airborne nanoparticles (NPs) to human health. To mimic pulmonary exposure, we have developed an air–liquid interface (ALI) exposure system for direct deposition of airborne NPs on to lung cell cultures. Compared to traditional submerged systems, this allows more realistic exposure conditions for characterizing toxicological effects induced by airborne NPs. The purpose of this study was to investigate how the deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…The quantified deposition on cell‐free inserts was approximately 14–21 times higher than compared to the cell‐containing inserts. A similar observation was made in a previous study, in which the deposition of Ag‐NPs was studied in the same ALI exposure system (Latvala et al, ) and in another study with Cu‐NPs (Elihn et al, ). The difference in deposited amount of Ni‐NP at cell‐free and cell‐containing conditions may be due to evaporation of liquid from the cell surface/medium below the cells at the cell‐containing conditions, which may prevent part of the Ni‐NP deposition.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The quantified deposition on cell‐free inserts was approximately 14–21 times higher than compared to the cell‐containing inserts. A similar observation was made in a previous study, in which the deposition of Ag‐NPs was studied in the same ALI exposure system (Latvala et al, ) and in another study with Cu‐NPs (Elihn et al, ). The difference in deposited amount of Ni‐NP at cell‐free and cell‐containing conditions may be due to evaporation of liquid from the cell surface/medium below the cells at the cell‐containing conditions, which may prevent part of the Ni‐NP deposition.…”
Section: Discussionsupporting
confidence: 84%
“…The difference in deposited amount of Ni‐NP at cell‐free and cell‐containing conditions may be due to evaporation of liquid from the cell surface/medium below the cells at the cell‐containing conditions, which may prevent part of the Ni‐NP deposition. Differences due to different quantification methods (gravimetrical vs. ICP‐MS) cannot be ruled out completely, but a previous in‐depth comparison for Ag‐NPs suggests that such a difference was rather small (Latvala et al, ). Therefore, to quantify the exposure concentrations as accurately as possible in this study, the total Ni mass was analyzed chemically from two cell culture inserts after each ALI treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combination of different OMICS methods can inform more thoroughly about ENMs MOA, which could be further used in ENM grouping approaches, as suggested by Riebeling et al (2017). Gene expression profiling of co-cultures and 3D cultures, as well as systems taking into account exposure route such as Air Liquid Interface cultures (Latvala et al, 2016;Kletting, 2017), better resemble the in vivo exposure scenarios, but before clear conclusions about the ENM MOA can be drawn, cell type-specific responses need to be addressed by omics approaches (Drasler et al, 2017;Snyder-Talkington et al, 2015). The importance of multi-omics approaches in the study of MOA of toxicants has been demonstrated in several toxicogenomics studies (Jayapal, 2012;Gavin, 2016).…”
Section: Molecular Effectsmentioning
confidence: 99%